(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
Hope Stewart describes some of the weapons and armour found near Dumfin hill. The three finds were all made at different times but within an mile and a half of one another. After a brief description of the surrounding area and some of the local legends associated with it, Stewart gives a detailed description of the items and the circumstances under which they were found. The first find is a peaked helmet that the author argues may have been from someone that took part in the Battle of Glenfruin (1602) that took place further up the river Fruin. The second find consisted of a trooper’s helmet, possibly from the same battle and an earlier bronze spearhead, which is similar to other spearheads that are already in the Society’s collection. The final items found in this area were an iron sword that had been bent in half, another large spearhead and a cup-like vessel. The author proposes that these items may have been part of a burial hoard but does not specify that a grave was found near Dumfin.